Risk Factors for Vestibular and Oculomotor Outcomes After Sport-Related Concussion. Issue 4 (July 2021) - Womble, Melissa N.; McAllister-Deitrick, Jamie; Marchetti, Gregory F.; Reynolds, Erin; Collins, Michael W.; Elbin, R.J.; Kontos, Anthony P.
Abstract : Objective: To investigate the association between risk factors and vestibular–oculomotor outcomes after sport-related concussion (SRC). Study Design: Cross-sectional study of patients seen 5.7 ± 5.4 days (range 0-30 days) after injury. Setting: Specialty clinic. Participants: Eighty-five athletes (50 male athletes and 35 female athletes) aged 14.1 ± 2.8 years (range 9-24 years) seeking clinical care for SRC. Interventions: Participants completed a clinical interview, history questionnaire, symptom inventory, and vestibular/ocularmotor screening (VOMS). Chi-square tests with odds ratios and diagnostic accuracy were used to examine the association between risk factors and VOMS outcomes. Main Outcome Measures: The VOMS. Results: Female sex (χ 2 = 4.9, P = 0.03), on-field dizziness (χ 2 = 7.1, P = 0.008), fogginess (χ 2 = 10.3, P = 0.001), and post-traumatic migraine (PTM) symptoms including headache (χ 2 = 16.7, P = 0.001), nausea (χ 2 = 10.9, P = 0.001), light sensitivity (χ 2 = 14.9, P = 0.001), and noise sensitivity (χ 2 = 8.7, P = 0.003) were associated with presence of one or more postconcussion VOMS score above clinical cutoff. On-field dizziness (χ 2 = 3.8, P = 0.05), fogginess (χ 2 = 7.9, P = 0.005), and PTM-like symptoms including nausea (χ 2 = 9.0, P = 0.003) and noise sensitivity (χ 2 = 7.2, P = 0.007) were associated with obtaining a postconcussion near-point convergence (NPC) distance cutoff >5 cm. The likelihood ratios were 5.93 and 5.14 for VOMS symptoms and NPC distance, respectively. Conclusions: Female sex, on-field dizziness, fogginess, and PTM symptoms were predictive of experiencing vestibular–oculomotor symptoms/impairment after SRC.